Small-scale spatial analysis of river corridor plants distribution in the San River valley (SE Poland) - Krawczyk, Rafał (Biodiversity: Research and Conservation, 2015)
Spatial distribution and habitat preferences of 55 river corridor plant species were analyzed on a local scale in the valley of a medium-size regulated river. The analysis was based on the results of a detailed mapping on a 50 km-long section of the Lower San River valley (366 cartogram cells of 1 square km). Selected species were divided into two groups: (1) strictly and (2) loosely confined to river corridors. River corridor plants were found throughout the valley (river channel, active and historical floodplain, older terraces, slopes); however, their frequency was diverse in particular areas. The highest concentrations were observed on the floodplain. Their number decreased towards the border areas of the valley. Species which were less confined to rivers were found more frequently in the valley (one species occupied, on average, 12.9% of grid cells), than plants strictly confined to the river system (one species occupied, on average, 5.9% of grid cells); however, the ranges of species of the second group were more restricted to the Holocene part of the valley, especially to the floodplain. River corridor plants were, ecologically, a highly diversified group. In the San river valley, they were found in riparian forests, pioneer ephemeral communities on the banks of water bodies, dry grasslands, meadows and old river beds; a lot of them grew in ruderal habitats.